2020
DOI: 10.1016/j.eucr.2019.101048
|View full text |Cite
|
Sign up to set email alerts
|

Complete response to nivolumab for metastatic renal cell carcinoma on hemodialysis patient; a case report

Abstract: A 73-year-old-male patient with hypertension and grade 3B chronic kidney disease underwent radical nephrectomy in the year 2000. As the renal function gradually worsened, the patient was started on hemodialysis in 2003. Eleven years after nephrectomy, the metastases were pointed out. The patient received sunitinib as first-line therapy. Thereafter, as the metastatic lesions became larger, we initiated nivolumab therapy (3 mg/m2 every 2 weeks). After 52 weeks, the metastatic lesions continued showing complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Ansari et al reported one patient on dialysis with metastatic RCC who experienced over 22 months of progression-free survival from immunotherapy with nivolumab [25]. Similarly, Ito and his colleagues confirmed a complete clinical response to nivolumab in an elderly patient with metastatic renal cell carcinoma and end-stage renal disease [26]. Moreover, proteolytic enzymes metabolize nivolumab and ipilimumab into polypeptides and amino acids.…”
Section: Table 1: Case Reports On the Occurrence Of Parotid Metastase...mentioning
confidence: 91%
“…Ansari et al reported one patient on dialysis with metastatic RCC who experienced over 22 months of progression-free survival from immunotherapy with nivolumab [25]. Similarly, Ito and his colleagues confirmed a complete clinical response to nivolumab in an elderly patient with metastatic renal cell carcinoma and end-stage renal disease [26]. Moreover, proteolytic enzymes metabolize nivolumab and ipilimumab into polypeptides and amino acids.…”
Section: Table 1: Case Reports On the Occurrence Of Parotid Metastase...mentioning
confidence: 91%
“…На настоящий момент однозначно сложно делать выводы о прогнозе для пациентов с терминальной стадией ХБП на фоне иммунотерапии злокачественного новообразования. Необходимо проводить дальнейшие исследования в данной группе для получения более репрезентативных выборок и оценки прогноза в зависимости от гистологического типа опухоли [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: иммунотерапия и хроническая болезнь почекunclassified